Schubert studies : problems of style and chronology - Badura-Skoda, Eva; Branscombe, Peter (Cambridge [Cambridgeshire] New York : Cambridge University Press, 1982)
This collection of articles, written by European, American and British scholars, clarifies problems of style and chronology in the music Schubert composed during the last decade of his life. Althought O. E. Deutsch's documentary biography and memoirs set new milestones in Schubert research, they left some problems of chronology unanswered. Some of the essays in this volume examine or re-examine these problems, using different methods. Robert Winter, in the longest essay, proposes numerous re-datings of works composed between 1822 and 1828 which result from a careful examination of types of paper and watermarks. Other contributors point out the limitations of applying stylistic criteria as the basis for the dating of individual works. The articles touch on all areas of Schubert's output, with the emphasis on his songs, theatre music, and orchestral and chamber works. Althought this book will be of primary interest to musicologists, and others interested in Schubert, the essays concerned with song and the theatre will also attract a wider readership.
Includes bibliographical references.
Includes index.
gedruktemuziek
Keywords: Schubert, Franz, -- 1797-1828